Comparative Law Concept of Restorative Justice Approach to Drug Abuser - M Sadam Husin; Maria Maya Lestari; Davit Rahmadan (Melayunesia Law, 2024)
Recent decades, the issue of drug protection has become one of the serious problems faced by many countries. The traditional approach that focuses on punishment often fails to reduce the number of drug referrals, and instead causes various other social problems. Therefore, an alternative approach that is more humane and effective is needed. Restorative justice offers a solution that focuses on recovery and reintegrating perpetrators into society. The type of research used in this study is normative legal research, using a comparative law method which examines the principles of law. In the conclusion, the author uses a deductive thinking method, namely a way of thinking that draws conclusions from a general statement or argument into a specific statement.